A phase I study of two dosing schedules of oral BI 847325 in patients with advanced solid tumors - Schöffski, Patrick; Aftimos, Philippe; Dumez, Herlinde; Deleporte, Amélie; De Block, Katrien; Costermans, Jo; Billiet, Maureen; Meeus, Marie-Anne; Lee, Chooi; Schnell, David; Goeldner, Rainer-Georg; Awada, Ahmad (Cancer chemotherapy and pharmacology, 2016)
Purpose This study determined the safety, maximum tolerated dose (MTD), pharmacokinetics, and preliminary efficacy of BI 847325, an oral dual MEK and Aurora kinase inhibitor, in patients with refractory solid tumors. Methods This trial recruited patients with an advanced non-resectable and/or metastatic solid tumor following failure of conventional treatment (NCT01324830; 1287.1). BI 847325 was administered orally, once daily (starting at 6 mg in the first cohort) using two dosing schedules: Schedule A (2 weeks on, 1 week off) and Schedule B (three periods of 5 days on, 2 days off). The primary objective was to identify the MTD of BI 847325 for both dosing schedules. Results Sixty-nine patients (Schedule A, n = 47; Schedule B, n = 22) were treated. The MTD was 120 mg per day for Schedule A (cumulative dose of 1680 mg per 3-week cycle) and 150 mg per day for Schedule B (cumulative dose of 2250 mg per 3-week cycle). Reversible hematologic and gastrointestinal toxicities were the most common dose-limiting toxicities. One patient with esophageal cancer (receiving 160 mg BI 847325, Schedule A) experienced a partial response for 67 days, and 21 patients ( n = 11 [23.4 %], Schedule A; n = 10 [45.5 %], Schedule B) had stable disease. Pharmacokinetic analyses showed at least bi-exponential disposition, with high inter-subject variability. There was no obvious relationship between markers of MEK or Aurora kinase inhibition and exposure to BI 847325 (exploratory analysis). Conclusions This first-in-human trial suggests that BI 847325 has an acceptable safety profile. However, due to insufficient drug exposure at the MTD to achieve relevant MEK inhibition, a decision was taken to halt the development of BI 847325.